2016
DOI: 10.1158/1535-7163.mct-16-0074
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and Antiangiogenic Effects of Aspirin-PC in Ovarian Cancer

Abstract: To determine the efficacy of a novel and safer (for gastrointestinal tract) aspirin (aspirin-PC) in preclinical models of ovarian cancer, in vitro dose-response studies were performed to compare the growth-inhibitory effect of aspirin-PC vs. aspirin on 3 human (A2780, SKOV3ip1, HeyA8), and a mouse (ID8) ovarian cancer cell line over an 8-day culture period. In the in vivo studies, the aspirin test drugs were studied alone and in the presence of a VEGF-A inhibitor (bevacizumab or B20), due to an emerging role f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 47 publications
6
37
0
2
Order By: Relevance
“…1 for the chemical structures of aspirin, indomethacin and soy PC). In the animal experiments, we used different procedures preparing Aspirin-PC as described previously (9,22). To make Indomethacin-PC stock for both cell culture and animal study, 8 gram of indomethacin (acid form) and 16 gram of Lipoid S-100 were subsequently dissolved into 60 ml of Acetone (Thermo Fisher Scientific, Inc., Fair Lawn, NJ, USA) in a 500-ml flat bottom round flask in 40˚C water bath.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 for the chemical structures of aspirin, indomethacin and soy PC). In the animal experiments, we used different procedures preparing Aspirin-PC as described previously (9,22). To make Indomethacin-PC stock for both cell culture and animal study, 8 gram of indomethacin (acid form) and 16 gram of Lipoid S-100 were subsequently dissolved into 60 ml of Acetone (Thermo Fisher Scientific, Inc., Fair Lawn, NJ, USA) in a 500-ml flat bottom round flask in 40˚C water bath.…”
Section: Methodsmentioning
confidence: 99%
“…MTT assay. MTT (purchased from Sigma-Aldrich; Merck KGaA) was added to the culture media of cells at a final concentration of 0.5 mg/ml for 4 h. The purple formazan product was then extracted into a solvent (90% isopropanol, 0.2% sodium dodecyl sulfate, and 0.01 mol/l HCl) which was then collected from the wells and read at an absorbance of 570 nm, as previously described (22).…”
Section: Methodsmentioning
confidence: 99%
“…An apparent discrepancy is that the concentrations required to exert these effects in cancer cells were significantly higher than that required to inhibit the activity of COX-1 or COX-2, suggesting the implications of other potential targets (12,13). Indeed, cell-based studies have demonstrated that aspirin inhibits cell proliferation, induces cell-cycle arrest and apoptosis in multiple cancer cell lines irrespective of COX-2 expression level (14)(15)(16)(17)(18). Aspirin can also sensitize cancer cell to TRAIL-induced apoptosis through a COX-2-independent mechanism (19).…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, the positive feedback between COX-2 and PGE2 is essential for expression of CXCR4 in cancer-associated MDSCs and the production of its ligand of CXCL2 in ovarian cancer [99]. Similarly, aspirin-PC inhibits cell proliferation, angiogenesis, and increased apoptosis in ovarian cancer cells and mouse models [100]. PGE 2 also functions as an immunosuppressive factor and contributed to the microenvironment of ovarian cancer by compromising the Toll-like receptor-mediated dendritic cell activation [101].…”
Section: Stress Inflammation and The Role Of Eicosanoidsmentioning
confidence: 98%